2009
DOI: 10.4012/dmj.28.121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bending on the mechanical properties of gold wrought-wire clasps: a non-linear finite element analysis

Abstract: The purpose of this study was to assess the effect of bending of dental gold alloy wires on the mechanical characteristics of wrought-wire clasps. We conducted a simulation of large deformation in straight wires by means of non-linear finite element (FE) analysis. A bending force increased the principal tensile stress on the outer surface of the bending corner and the compressive stress on the inner surface of the bending corner to their maximum values. After unloading with springback, a residual tensile stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The results of the present study showed that PEEK clasps of both dimensions (1 mm and 1.5 mm) with both undercuts (0.25 mm and 0.50 mm) had lower retentive force than Co-Cr clasps. However, Sato et al and others [ 28 , 29 , 30 , 31 , 32 ] suggested that the retentive force from 3 to 7.5 N is expected to have adequate retention for RPD. In this study, the retentive force at the end of the cycling test ranged, for the 1.0 mm PEEK clasps, from 1.91 to 10.51 N, and for the 1.5 mm thick clasps from 3.82 to 13.63 N. Accordingly, PEEK could be applied as clasps for RPD, as it provides adequate retention for RPD, even after six months of simulated usage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study showed that PEEK clasps of both dimensions (1 mm and 1.5 mm) with both undercuts (0.25 mm and 0.50 mm) had lower retentive force than Co-Cr clasps. However, Sato et al and others [ 28 , 29 , 30 , 31 , 32 ] suggested that the retentive force from 3 to 7.5 N is expected to have adequate retention for RPD. In this study, the retentive force at the end of the cycling test ranged, for the 1.0 mm PEEK clasps, from 1.91 to 10.51 N, and for the 1.5 mm thick clasps from 3.82 to 13.63 N. Accordingly, PEEK could be applied as clasps for RPD, as it provides adequate retention for RPD, even after six months of simulated usage.…”
Section: Discussionmentioning
confidence: 99%
“…The low cross-section, high curve, and long and thin clasp arms, in addition to the brittle nature of PEEK, create clasps that are easily deformed [ 26 , 36 , 39 ]. Accordingly, PEEK clasps are recommended to be engaged at a deep undercut, such as 0.50 mm, and be thicker than metal clasps to achieve acceptable stiffness and high resistance to deformation [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%